The failure patterns and analysis process of drill pipes in oil and gas well: A case study of fracture S135 drill pipe. (August 2022) - Yu, Zhiming; Zeng, Dezhi; Hu, Shurui; Zhou, Xiaomin; Lu, Wei; Luo, Jiang; Fan, Yunting; Meng, Keyu
Highlights: Main failure patterns of drill pipe are clarified. Analysis processes and methods of pipe failure are put forward. Fracture failure reasons and mechanism of Ni-plating S135 drill pipe are explored. Abstract: The failure of drill pipe occurs frequently in oil and gas wells and seriously affects the safety and efficiency of drilling operations. Therefore, this paper clarifies the main failure patterns and reasons of drill pipes, and puts forward the analysis process and method of pipe failures. The case of failure S135 drill pipe was investigated through a series of experimental tests and mechanical simulation. The results showed that the physical and chemical performance of pipe material met the requirements of API Spec 5DP-2020, and the fracture of pipe body belonged to overload ductile fracture. The drill pipe Ni-plating was damaged and the exposed matrix was corroded and scoured. The crack originated from the corrosion pit on the inner wall because of stress concentration, and extended along the circumference during the operation of lifting drill pipe for many times, and finally led to fracturing suddenly. In addition, some suggestions are given to prevent similar failures.